Mineral nutrition and its impact on the production of modern commercial laying hens (Research, Society and Development, 2022)
Most of the metabolic pathways of the animal organism require the participation of minerals, which play a fundamental role in several metabolic processes associated with maintenance and production functions of animals. When referring to the commercial laying hens, the minerals present functions mainly aimed at the development and composition of the bone structure and the performance of the birds, collaborating with the laying rate, feed conversion, egg weight, shell quality of eggs, and weight gain. However, there are concerns about the excessive use of minerals in poultry diet formulations, because when consumed in large amounts, besides increasing the cost of production, minerals may cause undesirable environmental effects. Given the assumption, the objective of this literature review was to address the impacts of mineral nutrition on the production of modern commercial laying hens, in addition to demonstrating the effects of minerals on egg quality and the environment.